IdP4IoT: Autenticação de Dispositivos da IoT em Provedores de Identidades SAML - Wangham, Michelle; Magno, Allex; Cardoso, Felipe (Anais do Workshop de Gestão de Identidades Digitais; 2019: Anais do IX Workshop de Gestão de Identidades DigitaisDO - 10.5753/wgid.2019.14024, 2019)
Internet of Things (IoT) covers hardware, software, and services infrastructure able to connect things to the Internet. Things need authentication for secure communication. Support for different authentication mechanisms for devices in the same infrastructure is an open problem in the context of IoT. This lightning talk describes a SAML Identity Provider able to authenticate IoT devices that is available for researchers at GIdLab from RNP. After authentication, IdP issues short-lived tokens in a portable and interoperable manner (SAML tokens).